Ethical perception of golden rice in Malaysia - Latifah Amin,; Noor Ayuni Ahmad Azlan,; Jamil Ahmad,; Abdul Latif Samian,; Mohamad Sabri Haron, (Environmental Management Society, Malaysia, 2010)
Golden rice was developed by the insertion of carrot gene into rice to solve vitamin A deficiency problem. Past studies have shown that consumer acceptance of genetically modified (GM) food is driven by many factors, of which moral aspects was found to be an important predictor or sometimes referred to as ‘a veto’ of support. The purpose of this paper is to examine how the Malaysian public in the Klang Valley region perceive the ethical aspects of golden rice. A set of questionnaire comprising of the ethical aspects of golden rice was distributed and completed by 208 Muslims residing in the Klang Valley area. Results of factor analysis showed that there are four components or dimensions of ethical aspects of golden rice. The dimensions are familiarity, perceived risks, denying benefits (if not carried out) and ethical acceptance. Cronbach alpha values for the all dimensions were good: familiarity (α=0.82), denying benefits (α=0.77), perceived risks (α=0.78) and ethical acceptance (α=0.84). Results from the survey has shown that majority of the respondents perceived the ethical aspects of golden rice as moderate except for the professionals who surprisingly claimed to have only low familiarity with golden rice while the clerical workers and the un-employed on the other hand, perceived high benefits and were highly accepting of the ethical aspects of golden rice